Coherent radiation of relativistic electrons in metamaterials based on the SRR/wire-grid unit cell in millimeter wavelength range; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 402 - Soboleva V. V. Veronika Vyacheslavovna; Naumenko G. A. Gennadiy Andreevich; Bleko V. V. Vitold Vladislavovich; Potylitsyn A. P. Alexander Petrovich (2017, 2017)
Title screen